Evaluation of Seven Oat (Avena sativa) Genotypes for Biomass Yield and Quality Parameters under Different Locations of Western Oromia, Ethiopia - Abuye Tulu; Mekonnen Diribsa; Worku Temesgen (Advances in Agriculture)
Recognizing the potential and importance of cultivating improved forage crops as a means of tackling the recurrent feed shortage facing the study area, seven oat genotypes were tested in randomized complete block design with three replications across two locations for three growing seasons (2014, 2015, and 2016). The study was aimed to evaluate dry matter (DM) and digestible organic matter yield and nutrient composition of oat genotypes. The study revealed that oat genotypes responded differently for herbage dry matter (DM) and digestible organic matter (OM) yield, and quality parameters in both study locations. Averaged over the seven oat genotypes, herbage DM and digestible OM yield. recorded at Bako were higher than Boneya Boshe location across the study periods. The ash (P > 0.05) content did not vary among oat genotypes at both testing locations, while variation was observed for DM, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), in vitro digestibility, and metabolizable energy (ME) constituents. In general, genotypes ILRI 6710 and 5453 showed higher herbage DM and digestible OM yield. Moreover, the two genotypes are also higher in their in vitro digestibility value and ME, DM, and CP contents but relatively lower in NDF, ADF, and ADL fiber constituents, and thus, they are recommended for wider cultivation.